Pemetaan Riset Grafit sebagai Adiktif dalam Biodiesel di Asia Tenggara dan Peluang untuk Indonesia Menggunakan Meta Analisis Review - Bidara Jelita Maha; Muhammad Ikhwan; Misnaini Misnaini (Pusat riset dan Inovasi Nasional, 2026)
The global energy crisis and climate change are driving the development of biodiesel as a renewable energy source. Graphite as an additive shows significant potential in improving the efficiency and reducing emissions of biodiesel. This study maps graphite-biodiesel research in Southeast Asia using a meta analysis of systematic reviews of 68 publications from Scopus, Web of Science, and ScienceDirect from 2015-2024. The results show that Malaysia leads in publication contributions (32%), followed by Thailand (28%) and Indonesia (18%). The optimal graphite concentration of 50 ppm increases brake thermal efficiency by 8.3% and reduces CO (15.7%), HC (12.4%), and smoke (18.9%) emissions, although there is an increase in NOx (6.8%). Palm oil methyl ester dominated the research (56%). Indonesia has strategic opportunities with abundant feedstock and graphite deposits, but faces challenges in research infrastructure, limited international collaboration, and the absence of an integrated national roadmap. Infrastructure investment, human resource strengthening, and industry academia collaboration are needed to accelerate national biodiesel research.